THE HISTORY AND EVOLUTION OF RHYTHMIC GYMNASTICS (Multidisciplinary Journal of Science and Technology, 2025)
Rhythmic gymnastics is a dynamic and graceful sport that combines elements of ballet, gymnastics, dance, and apparatus handling. This article provides an overview of the history and evolution of rhythmic gymnastics, tracing its origins, development, and key milestones. It explores how the sport transformed from a recreational activity to a competitive discipline, with a focus on its rise in popularity worldwide, its inclusion in the Olympics, and its continued growth today. The study highlights the athletes, coaches, and innovations that have shaped rhythmic gymnastics into the sophisticated and athletic sport it is today.